2012
DOI: 10.1038/clpt.2011.323
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Escalating Daily Doses of the Antituberculosis Drug Rifapentine in Healthy Volunteers

Abstract: Rifapentine (RPT) is an antituberculosis drug that may shorten treatment duration when substituted for rifampin (RIF). The maximal tolerated daily dose of RPT and its potential for cytochrome 3A4 induction and autoinduction at clinically relevant doses are unknown. In this phase I, dose-escalation study among healthy volunteers, daily doses as high as a prespecified maximum of 20 mg/kg/day were well tolerated. Steady-state RPT concentrations increased with dose from 5 to 15 mg/kg, but area under the plasma con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 32 publications
3
68
1
Order By: Relevance
“…Preclinical studies using mouse models have shown that regimens containing daily rifapentine can cure TB after only 3 months of treatment (16)(17)(18). A phase 1 clinical trial showed that rifapentine doses up to 20 mg/kg administered daily were well-tolerated and safe in healthy volunteers (19). A previous phase 2 clinical trial found 10 mg/kg of daily rifapentine to be as safe as, but not more efficacious than, 10 mg/kg of daily rifampin during the first 8 weeks of combination TB chemotherapy (20).…”
mentioning
confidence: 99%
“…Preclinical studies using mouse models have shown that regimens containing daily rifapentine can cure TB after only 3 months of treatment (16)(17)(18). A phase 1 clinical trial showed that rifapentine doses up to 20 mg/kg administered daily were well-tolerated and safe in healthy volunteers (19). A previous phase 2 clinical trial found 10 mg/kg of daily rifapentine to be as safe as, but not more efficacious than, 10 mg/kg of daily rifampin during the first 8 weeks of combination TB chemotherapy (20).…”
mentioning
confidence: 99%
“…The FDA-approved rifapentine dose administration for the treatment of tuberculosis, as part of a multidrug regimen, is 600 mg administered twice weekly for the first 2 months of therapy, followed by 600 mg administered once weekly for an additional 4 months (12). However, as part of efforts to optimize drug therapy for tuberculosis, rifapentine daily dosing regimens are also being explored (13,14).…”
mentioning
confidence: 99%
“…The LC-MS/MS method used for drug quantification was based on previously described methods (15). The analytes of interest were separated using a Waters BEH C8, 50-by 2.1-mm, and 1.7-m particle size column at ambient temperature.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…We incorporated DBS collection into a phase I dose escalation trial of RPT (15), with the goal of developing and validating an accurate and reproducible DBS assay to quantify RPT and desRPT, with the desRPT data supporting mathematical model building.…”
mentioning
confidence: 99%